Game of Privilege - Demas, Lane (The University of North Carolina Press, 2023)
This groundbreaking history of African Americans and golf explores the role of race, class, and public space in golf course development, the stories of individual black golfers during the age of segregation, the legal battle to integrate public golf courses, and the little-known history of the United Golfers Association (UGA)--a black golf tour that operated from 1925 to 1975. Lane Demas charts how African Americans nationwide organized social campaigns, filed lawsuits, and went to jail in order to desegregate courses; he also provides dramatic stories of golfers who boldly confronted wider segregation more broadly in their local communities. As national civil rights organizations debated golf’s symbolism and whether or not to pursue the game’s integration, black players and caddies took matters into their own hands and helped shape its subculture, while UGA participants forged one of the most durable black sporting organizations in American history as they fought to join the white Professional Golfers’ Association (PGA). From George F. Grant’s invention of the golf tee in 1899 to the dominance of superstar Tiger Woods in the 1990s, this revelatory and comprehensive work challenges stereotypes and indeed the fundamental story of race and golf in American culture.